Cd dopant effect on structural and optoelectronic properties of TiO2 solar detectors - Ilhan, Mustafa; Koc, Mumin Mehmet; Coskun, Burhan; Erkovan, Mustafa; Yakuphanoğlu, Fahrettin (Springer, 2021)
Al/n-Si/Ti1-xO2CdxO/Al photodiodes were produced using sol-gel and spin coating methods where CdO dopant was applied on different concentrations (x = 0.0; x = 0.01; x = 0.05; x = 0.10). Cd dopant effect upon structural, optical, photodiode and electrical properties was assessed. Scanning electron microscope and energy-dispersive spectra were used in the structural investigation. Optic properties were assessed using UV-Vis spectroscopy and bandgap energies of the photodiodes were calculated which were found to be between 3.25 and 3.36 eV. Increased bandgap energy was observed with increased CdO doping rate. Photodiode properties were assessed under varying daylight illuminations. Barrier height, ideality factor, dark current, linear dynamic rate, photosensitivity, photoresponsivity of the photodiodes were calculated. Electrical properties of the Al/n-Si/Ti1-xO2CdxO/Al photodiodes were calculated where conductance-voltage and capacitance-voltage plots were obtained. Corrective conductance-voltage and corrective capacitance-voltage graphs confirm that the electrical properties of the photodiodes depend on AC signal frequency. Frequency-dependent electrical characteristics were attributed to the density of interface states which were found to be between 10(11) and 10(12). Decreased density of interface state was found for increased AC signal frequency.
Keywords: Thin-Film; Optical-Properties; Electrical Characterization; Microstructure Properties; Silicon; Photodiodes; Diode; Gel; Interface; Electrode